Rapid Calibration of the Projector in Structured Light Systems Based on Brox Optical Flow Estimation - Yuxin Tang; Ping Sun; Hua Zhang; Nan Shao; Ran Zhao (Photonics, 2022)
In this work, we propose a rapid calibration technique for locating the projector in the structured light measurement system. Using Brox optical flow, the calibration of the three-dimensional (3-D) coordinates of the projector only requires two images captured before and after the motion of the calibration plate. The calibration principle presented in geometry depicts the relation between the position of the projector, the camera, and the optical flow caused by the movement of the calibration plate. Some important influences on accuracy are discussed, such as the environmental noises and the localization error of the camera and the calibration plate, illustrated by numerical simulations. The simulation results show that the relative errors of the projector calibration results are less than 0.8% and 1% in the case of the calibration images polluted by Gaussian noise of SNR of 40 dB and 20 dB, respectively. An actual experiment measured a square standard block, and a circular thin plate verifies the proposed method’s feasibility and practicality. The results show that the height distributions of the two specimens are in good agreement with their true values, and the maximum absolute errors are 0.1 mm and 0.08 mm, respectively.